Comparison of ionic calcium concentration and ethanol stability of goat's colostrums - Lin, M. J. (Malaysian Society of Animal Production, 2014)
Ionic calcium is one of the important factors affecting casein micelles stability in milk. Ethanol stability is widely used as an indicator of the casein micelles stability and a method of monitoring milk quality during cold storage. Both ionic calcium concentration and ethanol stability vary at different stages in lactation. The purpose of this study was to investigate the relationships between ionic calcium concentration and ethanol stability of goat's colustrums. Results showed that the average ionic calcium concentration and pH of goat's colustrums was higher than in bulk goat's milk. Ethanol stability was lower in individual goat's colustrums than in bulk goat's milk. The ethanol stability of colustrums decreased as the ionic calcium concentration increased.